PENGARUH LINEARITAS DAN RESIPROSITAS mAs TERHADAP INTENSITAS RADIASI PADA PESAWAT SINAR-X MERK SAMSUNG - Faesol, Ahmad; Utomo, Yusron Adi (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: This research is research quantitative with the approach obsevasional to know the influence of linearity and resiprositas mas to of the intensity of radiation on a plane x-rays owns the samsung in the radiology laboratory University of Aisyiyah Yogyakarta. Data analysis to the influence of linearity and resiprosity mAs to of the intensity of radiation uses the method densitometri with analysis on the outcome of a curve on the microsoft excel. The results of the study showed every the increase in mAs in a linear manner will increase output of the radiation intensity and density produced .While increase of the tube ( mA ) that it was offset to the decline in time exposure will produce the intensity and the constant density.Keywords : linearity of mas, reciiproscity of mas, intensitas radiradiation inensityasi